Ambiguous citizenship policies: Examining implementation gaps across levels of legislation in Jordan - Lillian Frost (Comparative Migration Studies, 2024)
Abstract Despite the prevalence of ambiguous citizenship policies that say one thing in law and another in implementing regulations, few studies have focused on systematically studying this type of implementation gap, particularly in contexts beyond North America and Europe. This largely has remained the case despite research on discursive policy gaps, which occur between a policy’s stated objectives and its laws, efficacy gaps, which describe when a policy’s outcomes fail to meet its goals, and compliance gaps, which reflect disparities between a state’s commitments to international law and its corresponding domestic policies. How can we advance conceptualizations of law-regulation implementation gaps? This paper proposes one approach by focusing on the content of domestic laws, on the one hand, and the content of related implementing regulations, on the other. When law-regulation discrepancies occur, they illustrate the agency of senior officials in writing this intentional ambiguity into different levels of legislation, challenging assumptions about institutional weakness and lower-level bureaucratic discretion as chief drivers of implementation gaps. The paper illustrates this concept by analyzing discrepancies between Jordan’s nationality and passports laws and their related implementing regulations, particularly regarding Gaza refugees’ access to passports, investors’ access to nationality, and Palestinian-Jordanians’ subjection to nationality withdrawals. These diverse cases of intentional ambiguity demonstrate that such gaps can serve to partially exclude or include a group and can occur with noncitizen and citizen as well as more or less vulnerable groups.